The effect of pharmacological modulation of autophagy on the gene expression of proinflammatory cytokines in THP-1 cells - Milošević Sara; Trajković Vladimir (Medicinski Podmladak, 2025)
Introduction: Autophagy is a process that cells use to eliminate old, unused, and damaged cytoplasmic components. The interaction between autophagy and cytokines could be one of the mechanisms that coordinate the activity of the innate and adaptive immune systems. Depending on the cell type and activation pathway, autophagy and pro-inflammatory cytokines have different mutual effects. Understanding the balance between these two processes is necessary to realize the therapeutic potential of autophagy regulation in various infectious, inflammatory, and autoimmune diseases. Aim: The aim was to investigate the role of pharmacological modulation of autophagy on the transcription of mRNA for the proinflammatory cytokines TNF, IL-1, and IL-6 in the monocytic cell line THP-1. Material and methods: The pharmacological modulation of autophagy by bafilomycin and trehalose was determined by measuring the autophagic flux, the conversion of LC3-II after blocking its degradation, by the immunoblot method. LC3 represents a marker of autophagy and LC3-II levels are thought to correlate with the number of autophagosomes. Using the RTqPCR, it was determined if bafilomycin and trehalose, through the modulation of autophagy, affect the transcription of genes for proinflammatory cytokines TNF, IL-1, and IL-6 by measuring mRNA concentrations of these cytokines. For the statistical analysis, a One-Sample t-test was used. Results: Immunoblot analysis confirmed that bafilomycin blocks autophagic flux by increasing intracellular levels of LC3-II. Trehalose increased the level of LC3-II, both in the presence and absence of bafilomycin, inducing LC3-II conversion in THP-1 cells. RT-qPCR analysis of THP-1 cells treated with trehalose showed a significant increase in transcription of the genes TNF, IL-1, and IL-6, whereas cells treated with bafilomycin exhibited a significant decrease in the transcription of these genes. Conclusion: Based on the results obtained in the research, it can be concluded that autophagy activates the expression of pro-inflammatory cytokines by increasing the transcription of their genes